PENYELIDIKAN POLA SEBARAN LIMBAH KARET BAWAH PERMUKAAN TANAH DENGAN METODE GEOLISTRIK - Juandi M Juandi M (Jurnal Ilmu Lingkungan, 2010)
Research has been conducted to determine the distribution pattern of rubber waste in the sub-surface by application of geoelectric methods. The reading showed that the resistivitydistribution were zero (at z = 0) before registration of rubber waste. The minimum value ofresistivity were of 13.1 ohm.m, while the maximum of 112 ohm.m. Distribution pattern of rubberwaste in the subsurface revealed that the minimum value of resistivity were of 20.8 ohm.m, whilemaximum of 122 ohm.m. The resistivity distribution before rubber waste application was of at z= 33 cm that accounts for the minimum value of resistivity 31.5 ohm.m, while maximum 124ohm.m. Distribution pattern of the waste in the subsurface come up with minimum and maximumof resistivity distribution of at z = 33 cm the were 7.11 ohm.m,and 96.6 ohm.m, respectively.